The Influence of Principal Supervision and Teacher Motivation on Teacher Performance at Kartika II-5 Elementary School - Erdalaila, Erdalaila; Andayani, Sri; Ahmaludin, Ahmaludin; Selamat, Selamat (Ensiklopedia: Jurnal Pendidikan dan Inovasi Pembelajaran Saburai, 2024)
The purpose of this study was to determine how much influence the principal's supervision and teacher motivation have on teacher performance at Kartika II-5 Elementary School. This research is descriptive quantitative research. The population in this study was all 53 teachers at Kartika II-5 Elementary School, Bandar Lampung. In determining the sample using total sampling technique. Data collection techniques in this research include observation, questionnaires and literature study. Each variable consists of 15 statement items which are measured using a scoring scale of 1 to 4 using a Likert scale. The data analysis technique in this research is validity testing, reliability testing, simple and multiple linear regression testing, and hypothesis testing. Based on data analysis, it was found that the variables of principal supervision and teacher motivation influenced teacher performance, both partially and simultaneously.